PERKEMBANGAN UMKM (USAHA MIKRO, KECIL, DAN MENENGAH) SERTA PENGARUHNYA TERHADAP KRISIS EKONOMI - Baihaqi, Baihaqi (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2023)
The development of MSMEs is one of the business fields that can develop and be consistent in the national economy. Micro, small and medium enterprises are one of the influences on the economic crisis. This research aims to determine the influence of the development of MSMEs on the economic crisis. In this research, library research is used, that is, in the process of collecting data, you do not need to go directly into the field but take various reference sources that support this research. This research is a qualitative research type. Data collection techniques, namely listening and taking notes, are important in carrying out data analysis by means of data reduction, data display and drawing conclusions developed in this research. The research results show that MSMEs have an important role in the regional economy, especially in driving regional economic activity and providing employment opportunities. So that an economic crisis can cause severe economic costs in the form of slow economic growth, decreased output, company bankruptcy, layoffs, instability in the financial sector and has a very strong impact on the economic development and growth of a region. The trade sector's contribution to GDP is the largest compared to other sectors.